Mouse ECG findings in aging, with conduction system affecting drugs and in cardiac pathologies: Development and validation of ECG analysis algorithm in mice. Issue 12 (10th December 2015) - Merentie, Mari; Lipponen, Jukka A.; Hedman, Marja; Hedman, Antti; Hartikainen, Juha; Huusko, Jenni; Lottonen‐Raikaslehto, Line; Parviainen, Viktor; Laidinen, Svetlana; Karjalainen, Pasi A.; Ylä‐Herttuala, Seppo
Abstract: Mouse models are extremely important in studying cardiac pathologies and related electrophysiology, but very few mouse ECG analysis programs are readily available. Therefore, a mouse ECG analysis algorithm was developed and validated. Surface ECG (lead II) was acquired during transthoracic echocardiography from C57Bl/6J mice under isoflurane anesthesia. The effect of aging was studied in young (2–3 months), middle‐aged (14 months) and old (20–24 months) mice. The ECG changes associated with pharmacological interventions and common cardiac pathologies, that is, acute myocardial infarction (AMI) and progressive left ventricular hypertrophy (LVH), were studied. The ECG raw data were analyzed with an in‐house ECG analysis program, modified specially for mouse ECG. Aging led to increases in P‐wave duration, atrioventricular conduction time (PQ interval), and intraventricular conduction time (QRS complex width), while the R‐wave amplitude decreased. In addition, the prevalence of arrhythmias increased during aging. Anticholinergic atropine shortened PQ time, and beta blocker metoprolol and calcium‐channel blocker verapamil increased PQ interval and decreased heart rate. The ECG changes after AMI included early JT elevation, development of Q waves, decreased R‐wave amplitude, and later changes in JT/T segment. In progressive LVH model, QRS complex width was increased at 2 and especially 4 weeks timepoint, and also repolarization abnormalities were seen. Aging, drugs, AMI, and LVH led to similar ECG changes in mice as seen in humans, which could be reliably detected with this new algorithm. The developed method will be very useful for studies on cardiovascular diseases in mice. Abstract : A new ECG analysis algorithm for analyzing mouse ECG was developed and found to be an accurate and feasible method. The ECG findings associated with aging, AMI and progressive LVH correlated well with the echocardiography findings and were found to resemble the ECG findings seen in humans.